Desde la tradición clásica hasta la cotidianidad femenina. Mitología, deseo y mujer en la poesía de Aurora Luque - Śmiłek, Ewa (Collectanea Philologica, 2022)
The classical legacy in contemporary Spanish poetry is evident, especially in the creation of Aurora Luque (Almería 1962), one of the best representatives of the neoclassical and culturalist trend in Hispanic poetry. This article aims to show the two aspects of her poetry: the recovery of the Greco-Roman tradition and the female voice that reconciles aesthetics and morality. To defend the feminine voice of everyday life, the poet reinvents and modifies the classical tradition offering us a new vision of mythology, topoi, themes and motifs from Antiquity.